Profitability and Value Addition of Mungbean Production in Barishal and Patuakhali Districts of Bangladesh - Kundu, N D; Uddin, M T; Sarkar, M M A; Toma, N I; Rashid, M M; Ahmed, S (Bangladesh Journal of Nuclear Agriculture, 2025)
Mungbean is a popular pulse in the diet because it is easily digestible, free from flatulence and easy to cook. Besides as mungbean is a short duration crop, it can fit in as a cash crop between major cropping seasons. Considering the overall importance of mungbean an extensive field survey was conducted for the assessment of profitability, value addition and constraints to mungbean production in two southern coastal districts: Barishal and Patuakhali. The study revealed that few farmers of these areas used chemical as well as organic fertilizers. The total cost incurred for mungbean production was Tk. 51850 ha-1 of which 50% is variable cost and the remaining 50% was fixed cost. The average return was Tk. 54143 ha-1. The benefit cost ratio on variable cost basis was 2.09 but on total cost basis it was 1.04. Considering the variable cost per kg production cost was Tk. 24.62 but on total cost basis it was estimated at Tk. 49.05 per kg. Producer share was 66% for husked mungbean and for fried packed mungbean it was 19.8% only. Disease infestation, insect attack, uneven and heavy rainfall, flash flood, unavailability of cultivating machines and inadequate labour during harvesting were found to be the major constraints to mungbean production in the study areas. Bangladesh J. Nuclear Agric, 38(2): 137-149, 2024